Synthesis of Tungsten Oxide Nanofibers Using Electrospinning Towards Gas Sensor Application - Hoang Yen, Do; Tran Ngoc Phu, Le; Thi Thanh Le, Dang (VNU Journal of Science: Mathematics - Physics, 2025)
A simple strategy was introduced to synthesize WO 3 nanofibers through an electrospinning process. In this work, tungstic acid, hydrogen peroxide and polyvinyl pyrrolidone were used as precursors. After electrospinning and drying the desired material was collected. The morphology and structure of the samples were analyzed by field-emission scanning electron microscopy (FESEM), energy-dispersive x-ray spectroscopy (EDS) mapping, and X-ray diffraction (XRD). The results show that the obtained materials are composed by nanofibers with uniform dimensions. The first tests of ammonia sensing were done from 250 to 450 °C; the WO 3 NFs sensor presented a good response of 3.48 to 500 ppm NH 3 at an operation temperature of 450 °C.